Measuring Affective and Behavioral Change-Evaluation & Research - Robinson, Dana; Robinson, James (Association for Talent Development, 1997)
This Info-line stresses the importance of laying the groundwork for measuring behavior and affective changes resulting from training programs. It concentrates on Kirkpatrick's third level of evaluation, behavior, and discusses specific techniques to track and measure changes in behavior.